A navigation-aided framework for 3D map views on mobile devices - Abubakar, Adamu; Sadegh, Ameri; Suhaimi, Ibrahim; Mantoro, Teddy (Praise Worthy Prize S.r.l., 2014)
The visualization of 3D objects on maps in mobile devices could enhance user perception of the objects on the map. However, in order to improve the interaction of the user with the mobile device that contains the 3D map for navigation, the path and location should be represented with a reasonable degree of accuracy and true to life. This paper utilizes a familiar concept of computational geometry that can be applied to the description of points and the path from one point to another: the Voronoi diagram conceptualizes the visualization of 3D objects on a 3D map in a mobile device used for navigation. The reason for considering Voronoi for this concept is that a system based on Voronoi was found to have a well-known geometric structure. This is similar to the fundamental construct of a navigation aid, which naturally evolves as a discrete set of points in moving from one location to another. The result of our concept could be implemented in the design of a device to aid navigation.